2017
DOI: 10.1155/2017/1059109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Propane and NaCl-SDS Solution on Nucleation Process of Mine Gas Hydrate

Abstract: In order to explore the method of accelerating hydration separation process to recover methane from mine gas, propane hydrate phase equilibrium was used to measure the equilibrium points of three kinds of mine gas in NaCl solution. Driving force was set as 1 MPa on this basis and high-pressure experimental apparatus of mine gas hydrate was used to carry out the nucleation kinetics experiments of mine gas hydrate for three gas samples in different concentrations of sodium chloride (NaCl) and sodium dodecyl sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Additionally, it can be observed that the induction time for the mixed hydrate formation in the presence of 5.56 mol % THF and 3.5 wt % NaCl with SDS as a co-promoter is the shortest (about 3.7 ± 0.4 h). This is because the repulsion between the head groups of SDS is stabilized by ions via electrostatic interaction, resulting in a dramatic reduction of interfacial tension. ,, Although the presence of amino acids decreases the induction time, the performance is not equal to that of SDS. This is because the amino acid structure, which contains electrophilic and nucleophilic sites, interacts with salt ions, reducing the hydrogen interaction between ions and water and thus lowering interfacial tension.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it can be observed that the induction time for the mixed hydrate formation in the presence of 5.56 mol % THF and 3.5 wt % NaCl with SDS as a co-promoter is the shortest (about 3.7 ± 0.4 h). This is because the repulsion between the head groups of SDS is stabilized by ions via electrostatic interaction, resulting in a dramatic reduction of interfacial tension. ,, Although the presence of amino acids decreases the induction time, the performance is not equal to that of SDS. This is because the amino acid structure, which contains electrophilic and nucleophilic sites, interacts with salt ions, reducing the hydrogen interaction between ions and water and thus lowering interfacial tension.…”
Section: Resultsmentioning
confidence: 99%
“…A study on methane hydrate formation without stirring using solutions of mixed NaCl (3 wt%) and SDS (0.1 wt%) found that the SDS micellization was diminished in NaCl solution, hence the promoting effect of SDS on hydrate formation is reduced [36]. While another study on propane/NaCl/SDS solution system showed a decreased induction time of hydrate formation in comparison with that for the SDS solution alone and hence, it was assumed that NaCl can increase the solubility of mine gas due to the presence of SDS micelles [37]. However, Ren et.…”
Section: Comparison Of P-t Profile Kinetics Of Ch 4 Gas Hydrate and T...mentioning
confidence: 99%